Heat pipes in sandwich structures for spacecrafts - Ng, Benson Guo Loong. (2011)
Thermal performance of two different heat pipes is investigated in this study to evaluate the efficiency and feasibility of embedding within simulated satellite substrates subjected to localized heat source. Both experiments and numerical methods were performed to determine the heat transfer capability. Various experimental setups were performed to determine the effect gravity exert on the performance of the heat pipe by inclining the setups at different angles. With the help of CFX software, numerical analysis were performed under similar real time conditions to determine the heat pipe performance in micro gravity environment, the effect of gravity with different inclination of the setup, the optimum number of embedded heat pipes within the substrate and the effect of distributing the heat pipe into different proportion in the heater plate and substrate plate.